Mathematical model to evaluate the effect of key operating conditions on proton exchange membrane fuel cell performance - Tan-Thich Do; Trung-Kien Vi; Cong-Son Pham (Center of Biomass & Renewable Energy (CBIORE), 2026)
Nowadays, proton exchange membrane fuel cells (PEMFCs) are regarded as a promising energy source for future applications due to their relatively low operating temperature, high efficiency, high power density, fast start-up capability, and zero emissions. During PEMFC operation, performance is influenced by numerous factors, including the key operating conditions. Therefore, developing a mathematical model to evaluate the effects of key operating conditions on PEMFC performance and energy efficiency is both necessary and significant in the PEMFCs. In this study, a mathematical model was developed using MATLAB/Simulink software and subsequently validated through a series of experiments to assess its accuracy. The results demonstrate that PEMFC performance is strongly affected by operating conditions, including operating temperature, operating pressure, membrane thickness, cathode gas type, cell active area, and the number of cells in the stack. In addition, water, heat generation, energy efficiency, and gas consumption were also considered and discussed detailed in the model. The findings indicate that operating temperature and pressure are the most influential parameters affecting PEMFC performance and energy efficiency. When the operating temperature increased, the cell performance improved due to enhanced electrochemical reaction kinetics and improved electrical conductivity. However, when the PEMFC operates at temperatures above 70 oC, a deterioration in performance is observed. This behavior can be attributed to membrane dehydration at elevated temperatures, which reduces proton conductivity and, consequently, lowers the output cell voltage. Increasing pressure reduces membrane resistance and interface contact resistance, leading to a decrease in voltage losses and an improvement in cell voltage. Therefore, the optimal operating tempearature was achieved at 70 oC in this study. At a current density of 0.5 A cm−2, the cell voltages are 0.550, 0.559, 0.564, 0.568, 0.571, and 0.574 V for anode operating pressures of 1.0, 1.5, 2.0, 2.5, 3.0, and 3.5 atm, respectively. Overall, this study provides a reliable and precise tool for predicting PEMFC performance under varying operating conditions.